2024
DOI: 10.1007/s40620-023-01841-3
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning for patients with end-stage kidney disease on dialysis: narrative review of the current evidence, and future considerations

S. F. Adenwalla,
P. O’Halloran,
C. Faull
et al.

Abstract: Patients with end-stage kidney disease (ESKD) have a high symptom-burden and high rates of morbidity and mortality. Despite this, evidence has shown that this patient group does not have timely discussions to plan for deterioration and death, and at the end of life there are unmet palliative care needs. Advance care planning is a process that can help patients share their personal values and preferences for their future care and prepare for declining health. Earlier, more integrated and holistic advance care p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The mortality among individuals under than 75 of age old, was higher in male than in female, while the mortality among those aged 75 and the old was similar between in genders. In numerous studies, cardiovascular and cerebrovascular diseases, as well as infectious diseases, have been identi ed as the primary comorbidities associated with mortality in hemodialysis patients (2,3,7,8,(19)(20)(21). Additionally, it has been observed that vascular diseases are more prevalent among male patients in Japan (22).…”
Section: Discussionmentioning
confidence: 99%
“…The mortality among individuals under than 75 of age old, was higher in male than in female, while the mortality among those aged 75 and the old was similar between in genders. In numerous studies, cardiovascular and cerebrovascular diseases, as well as infectious diseases, have been identi ed as the primary comorbidities associated with mortality in hemodialysis patients (2,3,7,8,(19)(20)(21). Additionally, it has been observed that vascular diseases are more prevalent among male patients in Japan (22).…”
Section: Discussionmentioning
confidence: 99%